Offers of appointments with nurse practitioners if a requested physician is unavailable. Issue 4 (26th September 2016) - Tinkler, Sarah; Sharma, Rajiv; Pal, Sudeshna; Susu‐Mago, Raven; Stano, Miron
Abstract: Background and purpose: Access to primary care remains a problem for a substantial portion of the U.S. population, and is predicted to worsen due to an aging population and the increasing burden of chronic diseases. Better integration of nurse practitioners (NPs) into the primary care workforce is a possible solution. We examine offers of appointments with NPs if a requested primary care physician is unavailable. Methods: Data are from a 2013 audit (simulated patient) study requesting appointment information from a national random sample of primary care physicians. Outcome variables include appointment offers, wait‐to‐appointment times, and appointment offers with alternate providers, including NPs. Conclusions: Of 922 calls to primary care physicians serving the general adult population, 378 (41%) offered appointments with the requested physician. Alternate providers were offered by 63 (7%), including nine offers with NPs (<1%). Mean wait‐to‐appointment for NPs (3.6 days) was statistically significantly shorter ( p ‐values < .01) than for requested physicians (22.5 days) or non‐NP alternate providers (23.9 days). Implications for practice: NPs are an important part of the primary care workforce, and new patients seeking primary care physicians may substantially reduce their wait times if an NP is offered.